Right or Wrong the memoirs of lord bell - Bell, Tim. (London Bloomsbury, 2014)
Right or Wrong is the much-anticipated memoir of Tim Bell, chairman of Bell Pottinger public relations and one of the best-known figures in UK media communications. Born into a resolutely middle-class suburban family during the war, he left school whilst still a teenager for a job as post-boy at ABC Television. Rising through the ranks of the burgeoning West End advertising industry, in 1970 he became a cofounder of the Saatchi & Saatchi agency, duly taking on the role of international chairman as the company achieved worldwide preeminence. In 1989, he formed the Chime Communications Company.
Includes index
Keywords: Tim Bell